Nouvelles convergences entre éthique environnementale et éthique animale : vers une éthique climatique non anthropocentriste - Michel Bourban; Lisa Broussois (VertigO)
This article investigates new convergences between animal ethics and environmental ethics by focusing on the effects as well as the causes of climate change. Its main objective is to show how a non-anthropocentric approach to climate ethics can increase the potential of collaboration between animal ethics theorists and environmental ethics theorists. It develops an approach that explains how animal ethics, environmental ethics and climate ethics can converge at the theoretical level on the common problem of livestock farming. Then it explains how, from a practical point of view, the vegetarian and vegan diet as well as the vegan lifestyle can be a solution to this common problem. Finally, it replies to major objections in order to develop arguments in favour of a duty not to consume animal products.